SMALL-SIZED TIMBER OR LARGE-SIZED TIMBER PLANTATION: A CASE STUDY IN VINH LINH DISTRICT, QUANG TRI PROVINCE - Thi Hai Hien, Vo; Dinh Hai, Le; Thi Van, Luu (Journal of Forestry Science and Technology, 2019)
The local authority and people in Vinh Linh district, Quang Tri province have made many efforts to promote sustainable management of forest plantation in direction of transferring from small-sized timber plantation to large-sized timber plantation. However, the role of household characteristics, social-economic factors and natural factors in forest planting decision of local people are still little understood. In this study, we surveyed 134 households in Vinh Linh district, Quang Tri province, in which there are 55 households planting for large-sized timber and 79 households not planting for large-sized timber. By applying “Cost-Benefit Analysis” method, the result of study showed that plantation for large-sized timber brings more benefits for local people than plantation for small-sized timber. In addition, the result of binary logistic regression analysis indicated that the factors, including: ‘Household understanding about policies related to planting large-sized timber’, ‘Assurance about sources of seedlings’, ‘Participation of household in FSC project’, and ‘Support by community related to large-sized plantation activities’ significantly influence household’s decision on planting large-sized timber in this study area. Therefore, it is essential to make right policies such as supporting policies (e.g. forest land policy, credit policy, technical supporting policy, benefit sharing policy…) in order to encourage and promote small households focusing more on large-sized timber production.